KUALITAS PENGEMBANGAN LKPD BERBASIS PBL BERBANTUAN CABRI 3D UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Mujahidawati; Phatona, Naifa Amanda; Falani, Ilham (Universitas Muhammadiyah Metro, 2024)
This study aims to describe the quality of the development of problem-based learning worksheets assisted by Cabri 3D to improve mathematical problem solving skills. The method in this research is Research and Development (RnD) using the Analysis, Design, Development, Implement, and Evaluation (ADDIE) model. The results obtained from material validation amounted to 97% and the results of design validation amounted to 92% with the category “very valid”. The level of practicality by educators was 91%, and the level of practicality by students was 85% and categorized as “very practical”. Obtained a student effectiveness rate of 85% categorized as “very effective”. For the average Pre-test results obtained with a score of 44.27 in the “low” category and the average Post-test results obtained with a score of 83.04 in the “high” category. The average result of the N-Gain value is 0.71 which is included in the “high” improvement category, while the percentage of N-Gain obtained is 71% in the “moderately effective” category. So that the development of Problem-based learning-based student worksheets assisted by Cabri 3D can improve mathematical problem solving skills by meeting good quality in terms of valid, practical, and effective.